Pengaruh Likuiditas, Profitabilitas, Inflasi, dan Suku Bunga Terhadap Return Saham - Marpaung, bintangsahala0203; Marpaung, Annaria Magdalena; Hasibuan, David H.M.; Siti Khoerunisa Sari, SE (Media Ilmiah Akuntansi, 2024)
The aim of this research is to determine the influence of interest rates, liquidity, profitability and inflation on stock returns of pharmaceutical companies listed on the IDX from 2016 to 2020. Purposive sampling was used in the sample collection process, and a sample of eight companies was included. Data sources accessed through secondary data. Data collection techniques include document analysis. Panel data regression analysis, t test, f test, classical assumption test, and the Eviews 10 application were used in this research. Panel data regression analysis of the data shows that, for the period 2016 – 2020, the variables CR, ROE, and Partial Interest Rates not significantly related to stock returns while Partial Inflation is significantly related to stock returns and Simultaneously the variables CR, ROE, Inflation and Interest Rates are Simultaneously related significantly between years 2016 and 2020. The variables mentioned above influence the R2 value by 27%, other factors not covered in this research influence the remaining 73%